2016
DOI: 10.1016/j.ejca.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of response after pre-operative radiotherapy in soft tissue sarcomas; the European Organisation for Research and Treatment of Cancer – Soft Tissue and Bone Sarcoma Group (EORTC – STBSG) and Imaging Group recommendations for radiological examination and reporting with an emphasis on magnetic resonance imaging

Abstract: At present, there is no standardised approach for the radiological evaluation of soft tissue sarcomas following radiotherapy (RT). This manuscript, produced by a European Organisation for Research and Treatment of Cancer-Soft Tissue and Bone Sarcoma Group (EORTC-STBSG) and Imaging Group endorsed task force, aims to propose standardisation of magnetic resonance imaging techniques and interpretation after neoadjuvant RT for routine use and within clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 39 publications
1
29
1
4
Order By: Relevance
“…Although the above mentioned late outcomes measures can be considered as robust endpoints, but they take years to observe. Surrogate early end-points provide an alternative assessment strategy, represented by outcomes such as the pathological evaluation of the resection specimen, wound complications, and potential signals from sophisticated imaging techniques (38)(39)(40)(41). There is a need for prospective clinical studies incorporating these aspects with the purpose of validation.…”
Section: Evidence-based Medicine On Fraction Size Total Dose and Ovementioning
confidence: 99%
“…Although the above mentioned late outcomes measures can be considered as robust endpoints, but they take years to observe. Surrogate early end-points provide an alternative assessment strategy, represented by outcomes such as the pathological evaluation of the resection specimen, wound complications, and potential signals from sophisticated imaging techniques (38)(39)(40)(41). There is a need for prospective clinical studies incorporating these aspects with the purpose of validation.…”
Section: Evidence-based Medicine On Fraction Size Total Dose and Ovementioning
confidence: 99%
“…Limitations of tumor size measurements has led to some pilot studies of FDG PET/CT and several show promising results although large scale evidence is challenging in this rare and heterogeneous group of tumors. Diffusion weighted MRI which is a simple, robust and non‐invasive technique has also been shown to detect and quantify early treatment in many tumor types but has not yet been proven in RPS although trials are underway …”
Section: Response Assessmentmentioning
confidence: 99%
“…Histopathological changes including necrosis, cystic change, haemorrhage, hyalinization, and fibrosis which occur following RT may cause tumors to increase in size resulting in pseudoprogression. With the exception of myxoid liposarcomas significant dimensional radiologic responses after preoperative RT are rare and have been reported as low as 0% . Miki et al showed that 31% of tumors increased in size by more than 10% but this was not associated with deterioration in local recurrence free survival, event free survival or overall survival.…”
Section: Response Assessmentmentioning
confidence: 99%
See 2 more Smart Citations